2017
DOI: 10.3389/fnsys.2017.00051
|View full text |Cite
|
Sign up to set email alerts
|

Regional Specific Evidence for Memory-Load Dependent Activity in the Dorsal Subiculum and the Lateral Entorhinal Cortex

Abstract: The subiculum and the lateral entorhinal cortex (LEC) are the main output areas of the hippocampus which contribute to spatial and non-spatial memory. The proximal part of the subiculum (bordering CA1) receives heavy projections from the perirhinal cortex and the distal part of CA1 (bordering the subiculum), both known for their ties to object recognition memory. However, the extent to which the proximal subiculum contributes to non-spatial memory is still unclear. Comparatively, the involvement of the LEC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…Consistent with this finding, Kuruvilla and Ainge ( 2017 ) showed that the involvement of the LEC in object recognition depended on the number of objects located in the environment suggesting that the LEC is involved when the animal has to perform a complex task (four objects) but not a simpler task (two objects). These results are also coherent with a recent study from Ku et al ( 2017 ) that showed a greater involvement of the LEC as a function of the number of items to be processed (5 vs.10 odors) in an odor recognition task.…”
Section: Ec and Object Explorationsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this finding, Kuruvilla and Ainge ( 2017 ) showed that the involvement of the LEC in object recognition depended on the number of objects located in the environment suggesting that the LEC is involved when the animal has to perform a complex task (four objects) but not a simpler task (two objects). These results are also coherent with a recent study from Ku et al ( 2017 ) that showed a greater involvement of the LEC as a function of the number of items to be processed (5 vs.10 odors) in an odor recognition task.…”
Section: Ec and Object Explorationsupporting
confidence: 92%
“…The notion that cognitive demand is an important factor that modulates the involvement of the MEC and LEC mainly arises from object exploration tasks. Interestingly, the importance of the LEC in high memory load conditions has been described in a recognition task involving odors (Ku et al, 2017 ) and in rat trace eyeblink conditioning (Morrissey et al, 2012 ). Whether task demand or task complexity is a relevant notion to account for a potential different involvement of the two sub-regions in navigation and between navigation and more spontaneous exploration tasks is an open question.…”
Section: Discussionmentioning
confidence: 98%
“…This property of SUB networks could potentially explain the propensity for CA1 populations to exhibit highly similar spatial firing patterns under circumstances in which animals explore two environments sharing shape, alignment, and spatial distribution of boundary cues ( Skaggs and McNaughton, 1998 ; Spiers et al, 2015 ; Grieves et al, 2016 ). Notably, this phenomenon has direct impact in promoting learning of nonspatial associations ( Morris et al, 1990 ; Grieves et al, 2016 ) and is consistent with recent findings revealing a role for proximal SUB, proximal CA3, and LEC in memory for exposure to specific odors ( Nakamura et al, 2013 ; Ku et al, 2017 ). Finally, the organization of CA1 place-specific firing according to the reference frame of the observable environmental boundaries may be enhanced by SUB “boundary vector cells” that encode specific environmental borders ( Lever et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…This might indicate that the LEC is the source of temporal information provided to distal CA1. Preliminary data from the Moser laboratory using population-level analyses of electrohysiological recordings partly support this hypothesis by reporting that LEC’s involvement within this frame depends on tasks’ demands, with free foraging tasks eliciting a stronger temporal representation in the LEC than continuous alternation/back-and-forth running tasks [ 69 ]; of note, such tasks’ demand dependency in the LEC were also reported in recent lesion and Arc imaging studies, albeit for the processing object and space information [ 70 , 71 ]. Our findings of a preferential involvement of distal CA1 in time processing depart from the standard model of episodic memory which, by extrapolation, predicts that temporal information would rather be processed by proximal CA1 because it mainly receives projections from the MEC, a part of the “where–when” pathway [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 86%